ANCIENT SCHWANNOMA: A GREAT MIMICKER OF ADRENAL TUMOUR - Low, Chee Koon; Hussein, Zanariah; Chua, Yi Jiang; Tan, Yee Ling; Paiman, Noorasmaliza Md (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Retroperitoneal schwannoma is a benign neoplasm arising from the neural crest cells. Pre-operative diagnosis of this rare tumour is often difficult due to its enormous size at the time of presentation and the lack of distinctive imaging phenotypes. We share a case of an incidentally discovered huge right periadrenal ancient schwannoma in an elderly patient who suffered from an underlying nasopharyngeal carcinoma. CASE A 70-year-old male was found to have a 15-cm right suprarenal mass when he underwent CT scan for the staging of nasopharyngeal carcinoma. He had no paroxysmal symptoms or hypertension. There were no features of Cushing syndrome. Endocrine evaluation showed no evidence of functioning pheochromocytoma or adrenocortical carcinoma. The patient underwent open adrenalectomy and tumour excision uneventfully. Pathology examination revealed a large ancient schwannoma consisting of spindle cells with nuclear and cytoplasmic S-100 positivity. CONCLUSION The pre-operative diagnosis of retroperitoneal schwannoma remains challenging despite the advances in imaging modalities. Th definitive diagnosis relies on biopsy or